BETWEEN ECOLOGY AND ECONOMY: HOW TO PROFIT FROM WILD ANIMALS WITHOUT EXPLOITING THEM - Maulana, Rheza (Buletin Veteriner Udayana, 2023)
The wild animal trade is a large-scale and profitable business. We understand that it is a business that generates economic income, and people actually profit from it. However, it comes with many negative implications, starting with the practice itself, which is deemed unethical and harmful to animal welfare. Excessive practice leads to biodiversity loss, nature imbalance, and even the spreading of infectious diseases. It begs the question: is profiting from wild animals worth all the negative implications to the ecology? What if there were other ways to generate income from wild animals without physically exploiting them? This paper tries to answer that question. Utilizing the literature review and exploratory descriptive methods It is done by researching similar issues, such as tree cutting for timber, which causes deforestation. And how people can earn money by preserving trees rather than cutting them down, through the carbon offset mechanism. The results showed that it is possible to profit from wild animals without physically capturing and selling them. It is suggested that we can develop a means of ethical wild animal tourism. Instead of selling the animals, we are selling the experience of finding them and watching them doing their natural activities in national parks. The more numbers of wild animals preserved in their natural habitat, the more abundant they are and the more appealing they are as a tourist destination. In a way, profits could potentially be higher and more effective than selling individual animals.